PERAN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) MELALUI SUB-PROGRAM 4 : DRUGS AND HEALTH DALAM MENANGANI PENYALAHGUNAAN NARKOBA DI MYANMAR - Adinda Chandra Fadhilla; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study discusses the roles of the United Nations Office on Drugs and Crime (UNODC) through sub-programme 4 : Drugs and Health in addressing drug abuse in Myanmar. Myanmar is the world’s second-largest producer of drugs with worrying cases of drug abuse followed by the government’s ineffective efforts in addressing the issue. Therefore, UNODC cooperates with the Government of Myanmar by carrying out its roles and following the mandate given to support member states in their efforts to address drug use by implementing scientific evidence-based program, using public health approach while fully respecting all human rights. This study aims to answer the research issues regarding the role of UNODC through sub-program 4 : Drugs and Health in addressing drug abuse in Myanmar.This research uses a qualitative method, Neo-liberalism Institutionalism approach, and theory of International Organization Roles with International System as the level of analysis. To analyse this case, the author collects data from books, journals, websites, and annual reports of UNODC. The findings of this study resulted in several things namely that UNODC have roles as instrument, arena and independent actors. UNODC’s roles as an instrument in Myanmar includes drug prevention, development of national drug policy, development of community-based service to raise awareness from the community, assisting in alternative development to help opium farmers escape the poverty trap of engaging in illicit crops and the risk of drug use, as an arena through a number of discussion and consultation and lastly, making its own decision in carrying out its activities in Myanmar as an independent actor. Keywords : Roles of United Nations Office on Drugs and Crime, Myanmar, Neo-Liberalism Institutionalism